Toxicity testing of selective laser melting technology towards production of titanium alloys (Ti6A14V) orthopaedic metal implant: primary analysis - Mohd Jan, Nurul Hafiza; Zulkifly, Ahmad Hafiz; Ibrahim, Mohd Zulfadzli; Zainal Abdullah, Muhamad Ezham; Mohd Zohari, Sarah Haryati; Che Seman, Che Nor Zarida; Omar, Mohd Afian (Universiti Putra Malaysia, 2025)
Selective Laser Melting (SLM) technology has garnered significant attention for producing customisable biomedical implants with complex structures and superior mechanical properties. It is increasingly used for tailoring orthopaedic implants, such as 6-hole plates. Titanium alloys (Ti alloys) implants are prevalent in orthopaedic surgery due to their excellent properties and bioinertness. A successful implant relies steadily on effective interaction with surrounding tissues. This study assesses the in vitro and in vivo biocompatibility of Ti alloy orthopaedic implants produced via SLM technology at the primary stage by examining cytotoxicity, genotoxicity and pyrogenicity. The results from the MEM elution assay indicated no reactivity (Grade 0) at 100 % concentration when exposed to SLM Ti alloys implant. The AMES test results showed that the number of revertant colonies treated with SLM Ti alloys implant did not exceed twice that of the negative control, regardless of metabolic activation. As for pyrogenicity analysis, the output shows that the absence of pyrogenic substance was noted after being introduced with SLM Ti alloys implant extractions. The positive and negative controls exhibited the expected action. In conclusion, the findings suggest that the production of Ti alloys orthopaedic implants through SLM technology do not induce toxic effects, confirming their biocompatibility and safety for orthopaedic use. This research highlights the promising biological safety of Ti alloys orthopaedic implants manufactured through SLM technology, with no observed toxicity at the primary stage